Specific features of adaptation practices of ethnic groups in the Republic of Tuva - Balakina, Galina F. (The New Research of Tuva, 2023)
Based on the data of the sociological survey of the population of Tuva conducted by the author in June and July 2023 (421 dwellers of towns and kozhuuns were interviewed), the article highlights the features of adaptation practices and the specifics of the adaptation processes of the ethnoregional groups in the Republic of Tuva (Tuvans and Russians). The purpose of the article is to identify and classify the peculiarities of adaptation practices of people living in Tuva, as well as to determine the distinctive features of ethnoregional models of integration into the processes of transformation in modern society. The author presents a classification of ten identified adaptation practices (models) on the basis of a list of adaptation strategies proposed by experts and published earlier. The practices are differentiated by the depth and speed of their integration into transformational processes (active, mobilizing and passive ones). The correlation of adaptation practices of the population with their income levels was studied. It has been found out that there is a significant credibility in the actions of the governments of Russia and Tuva although there are problems in the social well-being of the population. The study of the peculiarities of adaptation practices has highlighted the characteristic features of the responses of ethnic groups to the specifics of transformation processes in Tuva: the higher significance of enhancing education and qualifications, the application of social innovations among the Tuvans; job changes and higher levels of migration intentions among the Russians. The number of followers of passive practices is quite high. At the same time, the proportion of the “anticipating people” among the Tuvans is higher than among the Russians.